Let f"(x) = 2x - 6. Then,
f'(x) = integral ( f''(x) ) dx
= integral ( 2x – 6 ) dx
= 2 * (1/2)*x^2 – 6x + C
= x^2 – 6x + C.
Thus,
f'(–3) = (–3)^2 – 6(–3) + C
= 9 + 18 + C
= 27 + C.
But f'(–3) = –4 as given above. So we can solve for C as follows
f'(–3) = –4 = 27 + C.
This tells us that C = –4 – 27 = –31.
Therefore, f'(x) = x^2 – 6x – 31.
Next, we determine f(x). That is,
f(x) = integral ( f'(x) ) dx
= integral ( f'(x) ) dx
= integral (x^2 – 6x – 31) dx
= (1/3)*x^3 – 6*(1/2)*x^2 – 31x + K.
= (1/3)x^3 – 3x^2 – 31x + K.
So we have,
f(–3) = (1/3)*( –3)^3 – 3(–3)^2 – 31(–3) + K
= –9 – 27 + 93 + K
= 57 + K.
Since f(–3)= –1, we equate this to the previous equation to obtain K, that is:
f(3) = –1 = 57 + K.
This implies that K = – 58. Thus,
f(x) = (1/3)*x^3 – 3x^2 – 31x – 58.
Moreover, we have
f(3) = (1/3)*(3)^3 – 3(3)^2 – 31(3) – 58
= 9 – 27 – 93 – 58
= – 169.
2006-11-10 17:12:42
·
answer #1
·
answered by rei24 2
·
1⤊
1⤋
Given f"(x)=2x-6 ; f'(-3)=-4 ; f(-3)=-1
Find f '(x)and f(3)
f''(x) = 2x - 6
f'(x) = x² - 6x + C
f(x) = x³/3 - 3x² + Cx + D
f'(-3) = x² - 6x + C
-4 = (-3)² - 6(-3) + C
-4 = 9 + 18 + C
C = -31 so
f'(x) = x² - 6x - 31 and
f(x) = x³/3 - 3x² - 31x + D
f(-3) = x³/3 - 3x² - 31x + D
-1 = (-3)³/3 - 3(-3)² - 31(-3) + D
-1 = -9 - 27 + 93 + D
D = -58
f(-3) = x³/3 - 3x² - 31x - 58
f(3) = x³/3 -3x² - 31x - 58
f(3) = 9 - 27 - 93 - 58
f(3) = -169
So f'(x) = x² - 6x - 31 and f(3) = -169
2006-11-10 17:21:09
·
answer #2
·
answered by bourqueno77 4
·
1⤊
0⤋
f''(x) = 2x - 6
Integrate to get : f'(x) = x^2 - 6x + c1
f'(-3) = (-3)^2 - 6(-3) + c1 = -4
Therefore, c1 = -4 - 9 - 18 = -31
Thus, f'(x) = x^2 - 6x - 31
Integrate to get : f(x) = x^3 / 3 - 3x^2 - 31x + c2
f(-3) = (-3)^3 / 3 - 3(-3)^2 - 31(-3) + c2 = -1
Therefore, c2 = - 1 + 9 + 27 - 93 = -58
Thus, f(x) = x^3 / 3 - 3x^2 - 31x - 58
f(3) = 3^3 / 3 - 3(3)^2 - 31(3) - 58
= 9 - 27 - 93 - 58
= -169
2006-11-10 17:15:21
·
answer #3
·
answered by falzoon 7
·
2⤊
0⤋
A,B : constant
f"(x)=2x-6
ãâãf '(x)=x^2-6x+A
f '(-3)=-4
ãâãf '(-3)=(-3)^2-6*(-3)+A=-4
ãããA=-31
ãâ´ãf '(x)=x^2-6x-31
f '(x)=x^2-6x-31ã
ãâãf (x)=(1/3)x^3-3x^2-31x+B
f (-3)=-1ãâ
f (-3)
=(1/3)*(-3)^3-3(-3)^2
-31*(-3)+B=-1
ãããB=-58
ãâ´ãf (x)=(1/3)x^3-3x^2-31x-58
.f (x)=(1/3)x^3-3x^2-31x-58ãâ
f (3)
=(1/3)*(3)^3-3(3)^2-31*(3)-58
ãâ´ãf (3)=-169
2006-11-10 17:22:56
·
answer #4
·
answered by atomonados 1
·
1⤊
1⤋
from the condition you offered,we come to know that
the f(-3) has two answers ,one is -4,the other is -1
.it is contraditory.paradox is the word i want to use to describe your statement
2006-11-10 16:59:19
·
answer #5
·
answered by peterwan1982 2
·
0⤊
2⤋